MONITORING AND CONTROLLING TRAINER OF AUTOMATIC GRAIN DRYER MACHINE BASED ON PLC AND SCADA - Syahid, Mochamad Muqorrobin, Yusnan Badruzzaman, Setyoko, Nur Fatkhul Cholbi (Politeknik Negeri Semarang, 2022)
Grain drying is currently still using the traditional method of drying with solar thermal. One of the obstacles to rice production in Indonesia is the problem of the grain drying process. So far, Indonesian farmers still carry out traditional drying, only relying on the solar thermal to dry their grain, so that during the rainy season they will troubled in the drying process. Therefore, a trainer for a grain dryer machine with a small capacity is made so that it can be controlled by PLC and monitored using SCADA. The test results obtained that the weight of the grain before the 1000 gram test was tested with a drying time of 90 minutes, for the water content before drying was 18% after entering the drying process for 90 minutes, the weight of the grain became 927 grams and the water content after drying was 12.5%. At every 10 minutes the average weight loss of grain after the drying process is 5.9 grams and water content is 0.5%.